CASE STUDY: COMPLEMENTARY THERAPY TO INCREASE APPETITE IN STUNTED TODDLERS IN BANJARNEGARA DISTRICT - Fauziah Hanum Nur Adriyani; Surtiningsih; Feti Kumala Dewi, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
ABSTRACT Toddlers aged 1 - 5 years are a critical period, due to the accelerated growth and development of babies during this golden period. Efforts to deal with the problem of stunting in the form of supplementary feeding. In the problem of appetite disorders and frequency of eating, complementary therapy is given to increase appetite and frequency of eating. The purpose of this study was to determine the impact of providing complementary care with an increase in the increase in appetite of stunted toddlers. The method used in this research is a case study. The population in this study were stunted toddlers aged 3-5 years. The sample size in this study was 45 respondents who were given complementary care for 1 week and food record measurements were taken to determine the frequency of eating and appetite in stunted toddlers. Data analysis using univariate analysis. The results of the research that has been done that the toddler's appetite before the complementary care action has an average of 6.723, and the lowest score of eating portions is 5 mouthfuls / spoonful of the highest 7 mouthfuls / spoonful. While after having an average of 9.187 standard deviation 0.910, and the lowest score of eating portions of 9 mouthfuls / spoon and the highest 11 mouthfuls / spoon so that there is an effect of tuina massage on increasing toddler appetite after and before tuina massage.